eacher development policies as an official narrative of neoliberalism in Chile: A necessary contrast with teacher narratives. A necessary contrast with teacher narratives - Carrasco-Aguilar, Claudia (2025)
This study analyzes teacher development policies in contrast with the daily narratives of three teachers in Chile, who have had to overcome critical events in their teaching. A narrative study was conducted with interviews at two points in time (2017 and 2021). The results show discordance of both narratives and the scarce relevance of the policy for teacher professionalization. The relationship with the forms of counter-hegemony to educational neoliberalism, and the distance of educational policies from the personal dimensions of the teaching profession are discussed.